In-vivo-and in-vitro evaluation of the 5 French neonatal gastric tonometer - Thorburn, Kentigern (Department of Paediatrics and Child Health, 2017)
Introduction - Gastrointestinal tonometry has been widely used in adult practice for the early detection of shock and multi-organ failure. Its application in paediatrics has been limited by unsuitably large tonometers and doubt about the accuracy of measurements when saline is used as a tonometric fluid / vehicle for carbon dioxide (CO₂) equilibration. Objective - To evaluate the accuracy and reliability of the newly developed saline 5 French (5F) neonatal gastric tonometer. Study Design - (a) Direct in-vivo comparison of the 5F 0.9%saline tonometer (NST) with the recirculating gas tonometer (RGT) [the current reference standard in adult practice] in 10 Paediatric intensive care unit (PICU) patients, measuring tonometric PCO₂ (PtCO₂) and gastric intramucosal PCO₂ (PiCO₂). (b) In-vivo comparison of PiCO₂ measurements from two 5F tonometers in 10 PICU patients in unfed and fed state. (c) In-vitro comparison of reference PCO₂ to PtCO₂ values obtained using 0.9%saline and phosphate buffered saline in SF tonometers, and the RGT. Results - (a) Comparing the SF NST to RGT in 50 paired simultaneous measurements over PtCO₂ range 3.0 - 9.7kPa, the mean bias was -1.44kPa; limits of agreements (LOA) ±1.45kPa. The mean values of PtCO₂- derived gastric intramucosal pH (pHi) and PiCO₂-PaCO₂ difference differed significantly by -.11 and + 1.1kPa respectively (p<0.0001). (b) 100 paired 5F NST measurements (50 fed/ 50 unfed) over PtCO₂ range 2.48-11.1kPa were assessed. No significant difference was observed in PtCO₂: mean difference (standard deviation) - unfed 0.05kPa (0.36) (p=0.36); fed 0.05kPa (0.42) (p=0.43). (c) 20 consecutive measurements of PtCO₂ were obtained from the 5F NST, 5F phosphate buffered saline tonometer (PBST) and RGT at constant reference PCOi's of 2.5, 5.0, 7.5, 10.0kPa. The 5F NST underestimated the reference PCO₂ by a mean bias of 58% (LOA ±20%); the 5F PBST by 6% (LOA ±26%); while the RGT performed best with a mean bias of 5.7% and tight LOA ±1.5%. Conclusion - There are inherent problems in the methodology of the saline tonometry utilised in the 5F neonatal gastric tonometer. The use of the saline SF neonatal gastric tonometer to monitor gut perfusion in neonates and children should be interpreted with caution. Recirculating gas tonometry is the most accurate method of tonometry studied.